Ectopic spleen presenting with anemia and an abdominal mass in a dog - Prosser, Kirsten J. (Canadian Veterinary Medical Association, 2013)
An 11.5-year-old, neutered male, golden retriever dog that had previously had a splenectomy for benign disease 2 years prior to presentation was diagnosed with anemia and a large abdominal mass. Necropsy and histopathology identified the abdominal mass as ectopic splenic tissue.